Algebraic models in geometry - Félix, Y. (Yves) (Oxford graduate texts in mathematics, 2008)
This text is aimed at both geometers needing the tools of rational homotopy theory to understand and discover new results concerning various geometric subjects, and topologists who require greater breadth of knowledge about geometric applications of the algebra of homotopy theory.